Association of cow and quarter-level factors at a dry off and new intramammary infections in the dry period - R.T. Dingwell; K.E. Leslie; J.M. Sargeant; Y.H. Schukken (Kansas Agricultural Experiment Station Research Reports, 2002)
Data from 300 cows and 1,178 quarters were analyzed to determine factors associated with new intramammary infections (IMI). Teatends that were cracked and teats that did not close during the dry period were 1.7 and 1.8 times more likely to develop new IMI, respectively. The level of milk production on the last day of lactation significantly influenced new IMI and teat canal closure. More (P<0.05) cows (36%) producing $21 kg of milk developed new IMI than cows (18%) producing less. When milk production was 21 kg or higher, teat canals were 1.8 times more likely to remain open.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; Dry off; Mastitis; Teat ends